2022
DOI: 10.18178/ijiet.2022.12.6.1654
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of SPOC and Face-to-Face Courses and Factors Influencing the Effects

Abstract: Distance education has been widely used in universities due to the outbreak of Covid-19. SPOCs (Small Private Online Courses) have high enrollment and completion rates in higher education due to their ability to provide students with personalized deep learning. This study aims to investigate the learning effect of SPOCs and further explores the reasons that affect its effectiveness. The study found that: a) there is a certain difference in the learning effect between SPOCs and face-to-face courses; b) the lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Combined with the analysis of SPOC open education, the author demonstrated that four designs-that is, the teaching content system design, personalized learning strategy design, teaching activity design, and teaching evaluation system designare helpful to effectively improve education quality based on the mixed mode of the flipped classroom and SPOC teaching. Han et al [2] investigated the learning effect of SPOCs and found differences in their learning effect. Face-to-face courses can effectively improve students' learning ability by increasing their learning interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Combined with the analysis of SPOC open education, the author demonstrated that four designs-that is, the teaching content system design, personalized learning strategy design, teaching activity design, and teaching evaluation system designare helpful to effectively improve education quality based on the mixed mode of the flipped classroom and SPOC teaching. Han et al [2] investigated the learning effect of SPOCs and found differences in their learning effect. Face-to-face courses can effectively improve students' learning ability by increasing their learning interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some educational institutions have currently collaborated with Second Life platforms to build learning environments [4], such as some researchers focusing on the design and implementation of immersive learning environments [5]. The emergence of Metaverse meetings overcomes a series of problems that existed during previous virtual space interactions, such as too little interaction, screens blocking emotional communication [6], and poor learning outcomes [7]. It allows multiple users to use virtual reality technology to enter the virtual meeting room for interaction [8].…”
Section: Current Status Of Domestic and International Researchmentioning
confidence: 99%
“…The traditional teaching mode is transformed from face-to-face teaching to online teaching in times [15]. Due to the COVID-19 pandemic, face-to-face courses in most of educational institutes have changed to online courses [16]. Teaching modes such as online-offline mixture, SPOC, or MOOC are widely conducted in courses for improving teaching effects.…”
Section: B Course Construction System With Pblmentioning
confidence: 99%